Cost-effective and mobility-aware cooperative resource allocation framework for vehicular service delivery in the vehicular cloud networks. (24th September 2021) - Chowdhury, Mahfuzulhoq
The traditional cloud empowered vehicular networks cannot adequately meet the very low-latency prerequisites of real-time vehicular applications due to the absence of a suitable resource allocation algorithm. Most of the existing works on resource allocation in vehicular cloud networks did not take the heterogeneous cloud and network resources, service requirements, mobility, transmission strategies, workload processing and data transfer delay into account. To address these issues, this paper proposes a cost-effective and mobility-aware cooperative resource allocation (CEMC) method that aims to reduce the vehicular service result delivery delay for multiple intelligently connected vehicles applications over cloud empowered vehicular networks by taking into account cooperation among road-side units, vehicles, cloud servers, and mobile devices. This paper presents three different variants of our proposed framework. The evaluation results show the superiority of the proposed CEMC framework in terms of delivery delay, throughput, and pricing cost among all the variants of the proposed framework.